High-Squint FMCW SAR Imaging via Wavenumber Domain Algorithm. (2nd April 2021) - Bi, Hui; Li, Hao; Liang, Wei
Abstract : Nowadays, because the frequency modulation continuous-wave (FMCW) synthetic aperture radar (SAR) shows good potential in minimal transmission power and weight reduction of radar systems, it has been widely used and has become a common technique in modern short-range high-resolution earth observation. Different from the conventional pulsed mode, the stop-to-go approximation is not valid in FMCW SAR. Thus, the typical SAR imaging methods need to be modified to adapt the continuous-wave scheme in practical data processing. In this letter, a wavenumber domain algorithm (WDA) is derived and used for the FMCW SAR imaging under squint and high-squint cases. With the help of the exact scene recovery ability of the proposed WDA, we can achieve the accurate recovery of the considered scene even when using the collected high-squint data and hence obtain the well-focused high-resolution image of the considered scene. Experimental results with simulated and airborne data verify the effectiveness of the proposed method.